Customisable architectural systems - emerging types of integrated product deliveries in the building industry - Vibæk, Kasper Sánchez (Mass Customisation and Personalisation in Architecture and Construction, 2013)
Currently two main strategies can be said to dominate the building sector: 'building by pieces' and 'turnkey solutions'. Both strategies share some of the same problems architecturally as well as business-wise. Through the notion of system structures this chapter draws attention towards new more product-based organisational divisions in architecture and construction and discusses the emergence of integrated product deliveries (IPDs) as a new different strategy. IPDs are proposed as a means for handling design complexity by integrating design decisions into discrete industrialised products of matter, process and thought that can be configured and customised for a specific delivery and form part of unique construction projects. This can facilitate a more strategically focused design attention and the combination of such discrete subsystems into 'assemblages' can theoretically form complete build ings. This seems in many ways to be an intriguing alternative architecturally, business-wise and even seen from an environmental point of view. However, it also leads to the question whether a future architecture can be seen as more temporary 'assemblages' or configurations of (relatively) independent subsystems that interface materially and process-wise in the building.